Managerial Strategies in the Implementation of Inclusive Education for Equitable Distribution of Educational Rights - Munif, Muhammad; Permana, Muharirul Umam Adi (Journal of Educational Management Research, 2025)
National Education aims to develop the potential of students to become human beings of faith, piety, noble character, health, knowledge, creativity, independence, and responsibility, as stated in Law No. 20 of 2003, Article 3. Education must also provide opportunities for Children with Special Needs (ABK) to grow as a whole. According to Article 5, paragraph 2, citizens with physical, emotional, mental, intellectual, and/or social disabilities have the right to receive special education. Through inclusive education, ABK students can learn, play, and interact equally. This is affirmed in Permendiknas No. 70 of 2009, which requires each sub-district to have at least one school that provides inclusive education. This study aims to analyze and explore schools that implement inclusive education theoretically, as well as the implementation and implications of inclusive education in the equitable distribution of academic education rights. The method used is qualitative, a type of case study, with observation, interview, and documentation techniques. The results show four stages of implementation: student identification, determination of lesson plans, learning services, and evaluation. The implications include increased self-confidence, equal rights, reduced discrimination, as well as improved academics and growing empathy.